Rancangan dan Pengembangan Website serta Program Edukasi di RT 34 Kelurahan Karang Joang - Nahdiah Asrani; Randi Khairul Jamil; Reylanda Aran Apriza; Muhammad Aldiansyah; Muhammad Ricky Zakaria; Annisa Fatharani; Auliah Juliana Syavirah; Delvhi Attas; Eka Krisna Santoso; Muhammad Azka (Universitas Kristen Indonesia Toraja, 2025)
Community service is one of the implementations of the Tri Dharma of Higher Education aimed at providing tangible solutions to social problems. This program was conducted in RT 34, Karang Joang Subdistrict, Balikpapan, focusing on two main issues: the lack of transparency and security in tenant reporting and the limited access to education for children. The solutions implemented include developing a website-based information system to digitally manage tenant data and interactive educational programs in English and Mathematics. The results show that the website successfully enhanced transparency and security by reducing the potential for fraud cases. Furthermore, the educational programs improved children’s literacy and academic skills, particularly in Mathematics and English. Pre- and post-program analyses revealed significant improvements in the community's digital literacy. Thus, this community service program positively contributes to supporting the achievement of Sustainable Development Goals (SDGs), particularly in quality education and strong institutions. It is expected that this program can be replicated and further developed for broader communities. , , ,,